2015
DOI: 10.1002/2014ja020752
|View full text |Cite
|
Sign up to set email alerts
|

Structure and origins of the Weddell Sea Anomaly from tidal and planetary wave signatures in FORMOSAT‐3/COSMIC observations and GAIA GCM simulations

Abstract: The Weddell Sea Anomaly (WSA) is a recurrent feature of the austral summer midlatitude ionosphere where electron densities are observed to maximize during the local nighttime. In this study, tidal decomposition is applied to FORMOSAT-3 (Formosa Satellite)/Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) total electron content (TEC) and electron density observations between 2007 and 2012 to quantify the components dominating local time and spatial variation in the WSA region. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 27 publications
5
45
1
Order By: Relevance
“…They attributed the eastward propagation of these features as being the result of the dominant diurnal standing (D0 tide) and the eastward wavenumber 1 (DE1 tide), both of which appear to have eastward phase velocities when viewed in local time. Additionally, Chang et al (2015) suggested that the WSA not only can be reconstructed as the result of superposition between the D0 tide and DE1 tide but also westward wavenumber 2 (DW2 tide) and stationary planetary wave 1 (SPW1 tide) components in TECs, producing the characteristic midnight WSA peak. The D0, DE1, DW2, and SPW1 components were found to be an interannually recurring feature of the southern midto high-latitude ionosphere during the summer, manifesting as enhancements in electron density around 300-km altitude of the summer mid to high magnetic latitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed the eastward propagation of these features as being the result of the dominant diurnal standing (D0 tide) and the eastward wavenumber 1 (DE1 tide), both of which appear to have eastward phase velocities when viewed in local time. Additionally, Chang et al (2015) suggested that the WSA not only can be reconstructed as the result of superposition between the D0 tide and DE1 tide but also westward wavenumber 2 (DW2 tide) and stationary planetary wave 1 (SPW1 tide) components in TECs, producing the characteristic midnight WSA peak. The D0, DE1, DW2, and SPW1 components were found to be an interannually recurring feature of the southern midto high-latitude ionosphere during the summer, manifesting as enhancements in electron density around 300-km altitude of the summer mid to high magnetic latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism was confirmed using in situ CHAMP and GRACE observations by Chao and Luhr (2014), who reported that the diurnal eastward propagation of WSA-like features is caused by the D0 tide in the Southern Hemisphere and DE1 in the Northern Hemisphere. Recently, the tidal decomposition has been applied to TEC and/or electron density derived from inversion of TEC using radio occultation technique of FORMOSAT3/COS-MIC (F3/C), to quantify the components dominating local time and spatial variation in the WSA region (Chang et al 2015). Liu et al (2014) and Chang et al (2012) showed that the eastward drift of the three-dimensional F3/C electron density with HWM93 field-aligned winds agree with the eastward movements of the WSA.…”
Section: Introductionmentioning
confidence: 99%
“…(Heroux and Higgins 1977;Heroux and Hinteregger 1978;Heelis et al 1980;Dickinson et al 1984;Emery et al 2008;Wu et al 2012). With respect to the mid-latitudes, several recent model and observational studies showed that for manifesting the mid-latitude summer night anomaly, tidal components such as DE1 and DW2 in combination with SPW1 are predominant in the Northern Hemisphere, whereas D0 in combination with SPW1 are the major components in the Southern Hemisphere (Chen et al 2013;Jones et al 2013;Xiong and Lühr 2014;Chang et al 2015). However, origins of these non-migrating tides, especially the quantitative contribution from the lower atmosphere, are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al . [] reported that the features of the WSA can be reconstructed as the result of superposition between the D0, eastward wave number 1, DW2, and SPW1 components in F3/C TECs, producing the characteristic midnight WSA peak. According to these studies, we investigate the cause of the southern MSNA/WSA feature by using the IPE model with the magnetic apex coordinates and the better specified thermospheric field‐aligned neutral winds inferred from the global F3/C h m F 2 observations by using the wind bias correction scheme.…”
Section: Introductionmentioning
confidence: 99%